The role of private associations in enhancing voluntary work in Jeddah - Al-Harbi, Bayan Hamed (Journal of Humanities & Social Sciences, 2024)
The current study aimed to recognize the role of non-governmental associations in enhancing voluntary work and reveal the social, personal, financial, and educational challenges that encounter voluntary work at private associations. The study is classified as a descriptive one, using the social survey approach. The tool of study was represented in an electronic questionnaire for a sample that comprised (122) individuals in Jeddah. The study concluded many results, the most important of which was that the social field is the most practiced voluntary field by the sample individuals, with a (26.2%) ratio. The study indicated that the role of private associations in raising awareness of the voluntary work importance was high. Concerning the role of private associations in motivating volunteers and executing initiatives, providing safe environment and job safety was on the first rank, followed by association investment of volunteers’ capacities and capabilities. As for challenges that encounter voluntary work, the scarcity of qualified persons to manage voluntary work and low financial resources that are necessary for activating voluntary initiatives were the main financial and organizational challenges facing volunteers in private associations, in addition to volunteers; devotion to their family obligations, and ignoring the volunteers’ efforts that are the main social and personal challenges facing volunteers in private associations. The study introduced many recommendations, including the necessity of activating professional voluntary work, raising the ratio of skill-based volunteering, providing financial support for voluntary administrations that contribute to overcoming financial difficulties facing some private associations.